Gender equality and social inclusion in landscape management: the case of Mugina and Rugombo districts in Burundi - Nigussie, Likimyelesh; Osei-Amponsah, Charity; Havyarimana, A.; Atampugre, Gerald; Tilahun, Seifu A.; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
Initiatives in landscape management are designed as sustainable solutions to confront environmental and social challenges. Effective management hinges on recognizing the unique needs of local communities. This study examines how gender interacts with multiple identities, including marital status, socioeconomic status, and age, in conjunction with power dynamics. It underscores the significance of these elements in determining access to resources, the dissemination of knowledge and skills, and their role in influencing participation in decision-making processes vital for effective landscape management in the sub-Nyamagana watershed, situated in the Imbo plain of the Mugina and Rugombo districts in Burundi. This is qualitative research founded on data collected in June 2024, which includes eight key informant interviews (comprising four men and four women), 20 household interviews (equally divided between ten men and ten women), and eight focus group discussions (four conducted with male groups and four with female groups). The results demonstrate that the Burundi government has enacted laws to support environmental sustainability and sustainable development. However, the experiences shared by farmers highlight that age, socioeconomic factors, and power relations significantly impact their rights to resources, their ability to express their opinions, and their representation in landscape management, which in turn affects the effectiveness of landscape management initiatives. The three primary key results and recommendations are presented below.